DCAF2 is essential for the development of uterine epithelia and mouse fertility - Yang, Man; Wang, Kaixuan; Zhang, Liang; Zhang, Hongya; Zhang, Cong (Frontiers in Cell and Developmental Biology, 2024)
epithelium. DNA damage binding protein 1 and cullin 4-associated factor 2 (DCAF2), a conserved substrate receptor for the cullin 4-RING E3 ubiquitin ligase (CRL4) complex, is essential for maintaining genome stability by facilitating ubiquitin-mediated degradation of substrates. To better understand the physiological role of DCAF2 in female reproduction, we conducted a study using mice with conditional knockout (cKO) of Dcaf2 in the uterus using the progesterone receptor Cre (PgrCre/+) mouse model. Our results showed the cKO mice were completely infertile, despite having ovarian function. The cKO mice exhibited severely thin uteri, demonstrating notable defects in both the uterine epithelium and a lack of glands. In addition, there were impaired proliferation and differentiation of epithelial cells in the cKO mice, ultimately resulting in failed implantation. Moreover, through deciphering the uterine transcriptome of cKO mice, we revealed crucial differentially expressed genes associated with steroid signaling. Further experiments have demonstrated cKO mice exhibit elevated uterine PGR signaling and reduced estrogen receptor signaling, although the levels of progesterone and estrogen remained unaltered. These alterations may contribute to defects in epithelium. Overall, our findings highlight a previously unrecognized but indispensable role for DCAF2 in the development of uterine luminal and glandular epithelium by orchestrating PGR and estrogen receptor responses. Its deficiency in the uterus leads to mouse infertility.